Proceedings of the 2019 ACM International Conference on Interactive Surfaces and Spaces 2019
DOI: 10.1145/3343055.3359700
|View full text |Cite
|
Sign up to set email alerts
|

Tailored Controls

Abstract: a) (b) (c) Figure 1. We present a concept and a prototype of a system for creating personalized user interfaces from paper. Users can cut out preferred shapes from paper and add interaction functionalities to them. The paper shapes and the user's fingers are tracked by an RGBD camera mounted above the interaction surface ( Figure 1a). Our processing pipeline recognizes and measures manipulations of the shapes (Figure 1b), such as movements and touches, which can be mapped to certain functions according to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 42 publications
0
0
0
Order By: Relevance
“…As a result of user study, the users showed very positive impressions, e.g., enjoyment with the Do-It-Yourself (DIY) process. Becker, et al investigated the Tailored Controls approach that allows end-users to create personalized tangible user interfaces (TUIs) [10], in which the interface elements were made from plain paper while allowing the users to interact with software. The user study showed that the approach offered enjoyable and exciting experiences to the users.…”
Section: Related Workmentioning
confidence: 99%
“…As a result of user study, the users showed very positive impressions, e.g., enjoyment with the Do-It-Yourself (DIY) process. Becker, et al investigated the Tailored Controls approach that allows end-users to create personalized tangible user interfaces (TUIs) [10], in which the interface elements were made from plain paper while allowing the users to interact with software. The user study showed that the approach offered enjoyable and exciting experiences to the users.…”
Section: Related Workmentioning
confidence: 99%